Prediction of Alternative Solar Energy Utilization in Internet of Things Based Systems Using Random Forest Algorithm - Natsir, Fauzan; Abdurahman, Abdurahman; Sihombing, Redo Abeputra (Department of Informatics, Siliwangi University, Indonesia, 2025)
The continuous use of fossil energy is depleting available energy sources, necessitating the adoption of alternative or renewable energy sources, such as solar energy. With rapid technological developments, particularly in Internet of Things (IoT) applications such as ThingSpeak, new monitoring solutions are becoming available. ThingSpeak can be used to monitor and control device outputs efficiently. Controlling the work of the tool is one of the efforts to save energy. In this study utilizing the ThinkSpeak application with the support of the ESP 8266 component to send information obtained through the sensor to be displayed on the monitor screen and set the output on or off. So that electricity is used as needed. The results of this study show that the output of sensor readings that appear from the serial monitor via the Arduino application is almost the same as the display on ThinkSpeak. So that this tool can support energy saving both in terms of solar energy utilization, the tool work control system for utilization according to needs and can also monitor the condition of the battery whether it is still in good or bad condition